Biological activities of Taounates Pistacia lentiscus essential oil - Hafse, Maha; Benbrahim, Kawtar Fikri; Farah, Abdellah (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
The present work aims to evaluate the biological activities of the essential oil extracted from Pistacia lentiscuss leaves of Taounate. The minimum inhibitory concentration of this oil against of seven bacterial strains Gram+ and Gram- is performed by the macrodilution in liquid medium. The antioxidant activity is determined by the diphenyle-picryle-hydrazul (DPPH) test, and the anti-inflammatory activity is evaluated by using the plantar edema model induced in rabbit by the carrageenan. The results indicated that the foliar essential oil has an important antibacterial activity. Mycobacterium smegmatis is the most sensitive strain with a minimum inhibitory concentration (MIC) of 1/500. In addition, the results of the other tests showed that this oil has a low antioxidant and anti-inflammatory activity. The objective of this work has therefore been reached and the biological activities of the foliar essential oil of Taounates Pistacia lentiscus are evaluated.